PORTFOLIO OPTIMAL ANALYSIS: SIMPLE CAPM TESTING, COMPARING BENCHMARK PERFORMANCE TO MUTUAL FUNDS (EQUITY AND MIXED), AND COMPARING PORTFOLIOS PERFORMANCE THROUGH EX-POST AND BLACK-LITTERMAN MODEL ILLUSTRATION (A Case Study on Public Companies listed in Indonesia Stock Exchange and 53 mutual funds (equity and mixed) managed in 2010 – 2014) - Basuki, Abdullah (Jurnal Ilmiah Mahasiswa FEB, 2016)
This study deals with "asset allocation" which aims at finding out the kinds of positivist approach to portfolio choice. There are many kinds of models about portfolio analysis. In this study, the first done is trying to illustrate some models such as single index model, the CAPM and Black’s zero-beta CAPM which are models that are often discussed in investment topics. Further analyzes were to see replication of the descriptive part of the equilibrium model by simple test of the CAPM. There is a certain problematic phenomenon found in the model, furthermore the next step is to see the present conditions related to the indication of market efficiency by evaluating the performance of the benchmark to the portfolio managed by the investment manager involving both equity and mixed samples. Furthermore, it also aims about the mean-variance optimized portfolio at evaluating the performance of the portfolios using market data in ex-post. This study on illustrate portfolio optimization used 10 sample stocks of public companies listed on IDX and the stocks are often in the JII (Jakarta Islamic Index) related to sharia basis and the most liquid stocks traded on IDX. Furthermore, this study also used additional stocks in addition it came up to 40 samples when simple test of the CAPM was conducted. When evaluating the performance of mutual funds, this study used 53 samples (equity and mixed, sharia and conventional based), which have been managed in 2010 to 2014. There are t-statistics that was used to calculate the regression coefficient ̅ and ̅ in simple test of the CAPM and evaluate the performance of mutual funds. Last, turns out to the Black-Litterman model having positivist approach to portfolio choice is considered as better model from previous empirical results by illustrate the model also it can be taken as one of the alternatives besides other various models. Keywords: mean-variance, single index model, capital asset pricing model, benchmark performance, Black-Litterman.